2020
DOI: 10.1016/j.idcr.2020.e00968
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery thrombosis in COVID-19

Abstract: COVID-19 has been described to have association with hypercoagulable state and thromboembolic events in major blood vessels, pulmonary artery, major limb vessels causing limb ischemia. associated with neurological symptoms and complications including stroke. We present a unique case of renal artery thrombus formation secondary to COVID-19. To the best of our knowledge this is the fourth manuscript describing renal artery thrombosis with evidence on imaging studies in medical literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Ischemic events have a low incidence of around 0.1-1.4%, while splenic thrombosis has not been frequently described [100]. The data suggest that COVID-19 infections can cause macro and micro thromboembolic renal dysfunction and trigger a microvascular obstruction and infarction [101,102]. Idilman et.…”
Section: Complications Of Gastrointestinal Hepatic and Renal Systemmentioning
confidence: 99%
“…Ischemic events have a low incidence of around 0.1-1.4%, while splenic thrombosis has not been frequently described [100]. The data suggest that COVID-19 infections can cause macro and micro thromboembolic renal dysfunction and trigger a microvascular obstruction and infarction [101,102]. Idilman et.…”
Section: Complications Of Gastrointestinal Hepatic and Renal Systemmentioning
confidence: 99%
“…68 A few recent studies have also reported acute limb ischemia, renal artery thrombosis, retinitis, and optic neuritis in COVID-19 subjects and its survivors. [69][70][71] The reported neuromuscular complications like peripheral nerve injuries are predominantly idiopathic, though these can be secondary to the underlying systemic disease/ immune dysregulation, direct neural-invasion, or sometimes even related to the hospital-care (like prone positioning to treat ARDS). 72 MRI and high-resolution sonographic evaluation of the affected peripheral nerve is suggested, guiding the appropriate treatment and rehabilitative therapy in such individuals.…”
Section: Miscellaneous Manifestationsmentioning
confidence: 99%
“…88 Renal artery thrombosis and renal vein thrombosis have both been documented, including cases with associated renal infarction; however, these are likely rare events. [88][89][90][91][92]…”
Section: Micro or Macrovascular Injury/endothelial Activation Contributing To Ckd Riskmentioning
confidence: 99%